Gambaran persepsi mahasiswa terhadap vaksin COVID-19 di Kota Palu - Moh Yudawan Prasetya; Zwingly Christian Porajow; Windy M. V. Wariki (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2021)
Background: The COVID-19 vaccination program in Palu is still ongoing. However, the public hesitancy toward the COVID-19 vaccination might impact the continuity of the program. One of the roles of university students as social control and agents of change is mobilising the community so that the COVID-19 vaccination programme can be successful. It is necessary to know how students in Palu City perceive the COVID-19 vaccine.Aim: This study aimed to describe student perceptions of the COVID-19 vaccine in Palu City.Methods: The research used a descriptive method with a cross-sectional study design. The used survey is an adoption from the research on Public Perception of the COVID-19 Vaccine in South Sumatera. We carried out an online survey via Google Form. We analysed data univariately.Results: There were 125 respondents. The results showed that of 125 respondents, 96,8% respondents had positive perceptions, and the remaining 3,2% of respondents had negative perceptions of the COVID-19 vaccine.Conclusion: The vast majority of students in Palu City have a positive perception of the COVID-19 vaccine.Keywords: perception, students, COVID-19, COVID-19 vaccine